2015
DOI: 10.1039/c5tb00501a
|View full text |Cite
|
Sign up to set email alerts
|

New self-assembled supramolecular hydrogels based on dehydropeptides

Abstract: Supramolecular hydrogels rely on small molecules that self-assemble in water as a result of the cooperative effect of several relatively weak intermolecular interactions. Peptide-based low molecular weight hydrogelators have attracted enormous interest owing to the simplicity of small molecules combined with the versatility and biocompatibility of peptides. In this work, naproxen, a well known non-steroidal anti-inflammatory drug, was N-conjugated with various dehydrodipeptides to give aromatic peptide amphiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…In our laboratory, we have investigated peptides containing dehydroamino acids (dehydrophenylalanine-∆Phe, dehydroalanine-∆Ala, dehydroaminobutyric acid-∆Abu) as alternatives to D-amino acids, not only to provide proteolytic stability but also for the reduced conformational flexibility of the peptide backbone. We have recently reported that dehydrodipeptides capped on the N-terminus with naproxen self-assemble into nanostructured hydrogels [18,22]. These peptide conjugates were found to be resistant to proteolysis by chymotrypsin, whereas the corresponding canonical dipeptide-naproxen Pharmaceutics 2020, 12, 122 3 of 18 conjugates undergo proteolysis readily under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, we have investigated peptides containing dehydroamino acids (dehydrophenylalanine-∆Phe, dehydroalanine-∆Ala, dehydroaminobutyric acid-∆Abu) as alternatives to D-amino acids, not only to provide proteolytic stability but also for the reduced conformational flexibility of the peptide backbone. We have recently reported that dehydrodipeptides capped on the N-terminus with naproxen self-assemble into nanostructured hydrogels [18,22]. These peptide conjugates were found to be resistant to proteolysis by chymotrypsin, whereas the corresponding canonical dipeptide-naproxen Pharmaceutics 2020, 12, 122 3 of 18 conjugates undergo proteolysis readily under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several low molecular weight dehydrodipeptide hydrogelators were prepared and studied as new drug delivery systems. 49,50 Thus, the combination of phenolic or catecholic moieties with dehydroamino acids can be a valuable approach to the development of new biologically active compounds.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…Both isomers of the dehydroresidues occur in nature and they often exhibit different biological properties [7,9]. α,β-Dehydropeptides are more stable and resistant toward proteolytic degradation and thus could be used to design synthetic analogs of biologically active peptides [10][11][12]. According to the literature on α,βdehydropeptides, the (Z)-dehydrophenylalanine [13][14][15] is the most often studied residues.…”
Section: Introductionmentioning
confidence: 99%